The functional and technological potential of guabiroba fruit (Campomanesia xanthocarpa O.Berg) and its application in dairy products and innovative foods using by-products with a focus on the use of emerging technologies - Prestes, Amanda Alves (2023)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Alimentos, Florianópolis, 2023.